Efficiency of counselor in conducting various cultural counseling services - Kamarul Md Shah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Multicultural counseling competencies are one of the important aspects to the practice of counselors in order to provide effective counseling services. However, studies of multicultural counseling competencies among counselors in Malaysia are still not sufficient to serve as a referral source. This study aims to identify the level of multicultural counseling competencies as a whole and by domain competence as practiced by counselors in Malaysia. The study also aims to identify the difference levels of multicultural counseling efficiency of the respondents based on gender, level of education, and professional experience in the counseling area. The study consisted of 102 counselors who were randomly selected in Malaysia and served as counselors at the Ministry of Education. The instrument used in this study was developed by the researchers based on the theory, interviews, expert panel, and also reviews of literature.The findings showed that the overall mean score of the respondents’ multicultural counseling competency level is at a high level. Although in terms of the overall level of efficiency is at a high level, the knowledge domain level is at the highest level compared to the domain of consciousness and domain of skills. The study also found that there were significant differences in the level of multicultural counseling competencies among the respondents based on the level of education. In contrast, there were no significant differences in the efficiency of the respondents based on gender and professional experience. This study suggested implications for counseling training in improving the efficiency of multicultural counseling.